Bacterial patterns and antibiotic susceptibility among pus culture in dr. Zainoel Abidin General Hospital, Banda Aceh - KEUMALAHAYATI, MEUTIA; HAYATI, ZINATUL; MAELANI, IMELDA; RIDWAN, AZWAR; RAHMAWATI, CUT VIKA; MULIANA, DESI; PUTRI, FARAH DHITA ANISSA; MAHDANI, WILDA (Universitas Syiah Kuala, 2025)
The collection of pus samples is crucial for identifying serious bacterial infections. Accurate identification of the pathogen and selection of the appropriate antibiotics are essential for effective treatment. This study used a descriptive retrospective method to investigate pus specimens bacterial patterns and antibiotic susceptibility at dr. Zainoel Abidin General Hospital in Banda Aceh in 2023. Out of 1,274 examined pus specimens, 782 yielded positive cultures, revealing 61 bacterial species, predominantly Escherichia coli (22%), Staphylococcus aureus (16%), and Pseudomonas aeruginosa (9%). Gram-negative bacteria constituted 70.20% of the isolates. High antibiotic susceptibility rates were observed for Vancomycin (98%) and Linezolid (98%) in Gram-positive bacteria, while Amikacin (86%) and Meropenem (74.74%) were effective against Gram-negative bacteria. Notable resistance was found in Methicillin-resistant S. aureus (81%) and E. coli resistant to third-generation Cephalosporins (55%). These findings underscore the importance of monitoring bacterial patterns and antibiotic resistance for improved infection management at dr. Zainoel Abidin General Hospital, Banda Aceh.